2018
DOI: 10.1155/2018/7462839
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antioxidant Potential and Effect of a Glutathione‐Enhancer Dietary Supplement on Selected Rat Liver Cytochrome P450 Enzyme Activity

Abstract: Background There is considerable evidence that many people take dietary supplements including those of herbal origin as an alternative therapy to improve their health. One such supplement, with an amalgam of constituents, is CellGevity®. However, the effect of this dietary supplement on drug-metabolizing enzymes is poorly understood, as it has not been studied extensively. Therefore, we investigated the effect of CellGevity dietary supplement on selected rat liver microsomal cytochrome P450 (CYP) enzymes, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 39 publications
0
17
3
Order By: Relevance
“…In the present study (after the 30-day treatment period), Cellgevity® signi cantly increased the activity of rat CYP1A1/2, CYP2C9 and CYP2D6. These results differ from what we earlier reported (11), where Cellgevity® signi cantly inhibited rat CYP3A4, CYP2B1/2B2 and CYP2C9 after a 7-day treatment period.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…In the present study (after the 30-day treatment period), Cellgevity® signi cantly increased the activity of rat CYP1A1/2, CYP2C9 and CYP2D6. These results differ from what we earlier reported (11), where Cellgevity® signi cantly inhibited rat CYP3A4, CYP2B1/2B2 and CYP2C9 after a 7-day treatment period.…”
Section: Discussioncontrasting
confidence: 99%
“…The commonest of these interactions appear to occur at the level of drug metabolism; especially with liver microsomal enzymes. We earlier reported that Cellgevity® signi cantly inhibited rat liver CYP3A4, CYP2C9 and CYP2B1/2B2 after a 7-day treatment period (11). On the premise that CYP3A4 was inhibited by Cellgevity® in our earlier research, the current study also sought to determine the effect of Cellgevity® on the pharmacokinetics of carbamazepine (a CYP3A4 substrate) after a 14-day treatment period in SD rats.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations